1999
DOI: 10.1016/s0749-6419(98)00073-4
|View full text |Cite
|
Sign up to set email alerts
|

Strong discontinuities and continuum plasticity models: the strong discontinuity approach

Abstract: The paper presents t he Strong Discontinuity A pproach for the a n alysis and s i m ulation of strong discontinuities in solids using continuum p lasticity m o d els. Kinematics of weak and strong discontinuities are discussed, and a regularized kinematic state of discontinuity i s p r o posedasamean to model the f o r m ation of a strong discontinuity a s t he c o llapsedstate o f a w eak discontinuity (w i t h a c haracteristic bandwidth), induced by a bifurcation of the stress-strain eld, which p r o pagate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
172
0
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 217 publications
(186 citation statements)
references
References 24 publications
2
172
0
12
Order By: Relevance
“…Several authors [22,23,24,25,26,27,28] have found analytical and geometrical solutions for the orientation of the discontinuity bands resulting from elasto-plastic models using di¤erent strategies. All of them seek their solutions after the so-called localization condition, which implies the loss of material ellipticity of the constitutive relation and is shown to be a necessary condition for the appearance of weak discontinuities and localized failure to take place.…”
Section: Orientation Of the Shear Band Discontinuitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors [22,23,24,25,26,27,28] have found analytical and geometrical solutions for the orientation of the discontinuity bands resulting from elasto-plastic models using di¤erent strategies. All of them seek their solutions after the so-called localization condition, which implies the loss of material ellipticity of the constitutive relation and is shown to be a necessary condition for the appearance of weak discontinuities and localized failure to take place.…”
Section: Orientation Of the Shear Band Discontinuitiesmentioning
confidence: 99%
“…In fact, they can be shown to be necessary conditions for the occurrence of bifurcation and localization of the strain …eld, with bounded stresses and decohesion in the limit case along a localization band (or a regularized strong discontinuity). This is why the term strong discontinuity condition was used in reference [28] for it. However, it applies to localization bands (limited by weak discontinuities) and strong discontinuities alike.…”
Section: Orientation Of the Shear Band Discontinuitiesmentioning
confidence: 99%
“…A recently developed phenomenological model (Regueiro and Borja, 1999;Borja and Regueiro, 2001) extends the strong discontinuity approach developed by Simo and co-workers (Simo et al, 1993;Simo and Oliver, 1994;Armero andGarikipati, 1995, 1996;Oliver et al, 1999) to pressure sensitive, nonassociative plasticity models. The strong discontinuity approach yields mesh-independent ®nite element solutions without introducing a material length scale and without requiring special mesh alignment strategies.…”
Section: Introductionmentioning
confidence: 97%
“…More recently, the XFEM [26,27] was introduced as an enrichment of finite elements through the notion of partition of unity. Finally, the strong discontinuity approach [28,29] provides an element formulation that embed the displacement jump in its interior. The implementation of such enrichments requires the use of auxiliary tracking techniques in 2D and 3D.…”
Section: Introductionmentioning
confidence: 99%